Oral modified release morphine for breathlessness in chronic heart failure: a randomized placebo‐controlled trial. (6th August 2019) - Johnson, Miriam J.; Cockayne, Sarah; Currow, David C.; Bell, Kerry; Hicks, Kate; Fairhurst, Caroline; Gabe, Rhian; Torgerson, David; Jefferson, Laura; Oxberry, Stephen; Ghosh, Justin; Hogg, Karen J.; et al.
Abstract: Aims: Morphine is shown to relieve chronic breathlessness in chronic obstructive pulmonary disease. There are no definitive data in people with heart failure. We aimed to determine the effectiveness and cost‐effectiveness of 12 weeks morphine therapy for the relief of chronic breathlessness in people with chronic heart failure compared with placebo. Methods and results: Parallel group, double‐blind, randomized, placebo‐controlled, phase III trial of 20 mg daily oral modified release morphine was conducted in 13 sites in England and Scotland: hospital/community cardiology or palliative care outpatients. The primary analysis compared between‐group numerical rating scale average breathlessness/24 hours at week 4 using a covariance pattern linear mixed model. Secondary outcomes included treatment‐emergent harms (worse or new). The trial closed early due to slow recruitment, randomizing 45 participants [average age 72 (range 39–89) years; 84% men; 98% New York Heart Association class III]. For the primary analysis, the adjusted mean difference was 0.26 (95% confidence interval, −0.86 to 1.37) in favour of placebo. All other breathlessness measures improved in both groups (week 4 change‐from‐baseline) but by more in those assigned to morphine. Neither group was excessively drowsy at baseline or week 4. There were no between‐group differences in quality of life (Kansas) or cognition (Montreal) at any time point. There was no exercise‐related desaturation and no change between baseline and week 4 in either group. There was no change in vital signs at week 4. The natriuretic peptide measures fell in both groups but by more in the morphine group [morphine 2169 (1092, 3851) pg/mL vs. placebo 2851 (1694, 5437)] pg/mL. There was no excess serious adverse events in the morphine group. Treatment‐emergent harms during the first week were more common in the morphine group; all apart from 1 were ≤ grade 2. Conclusions: We could not answer our primary objectives due to inadequate power. However, we provide novel placebo‐controlled medium‐term benefit and safety data useful for clinical practice and future trial design. Morphine should only be prescribed in this population when other measures are unhelpful and with early management of side effects.